NATURAL CATHEPSIN INHIBITOR TO INHIBIT MILKFISH DETERIORATION DURING CHILLING STORAGE - Tati Nurhayati; Wini Trilaksani; Mohammad Zaenuri (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Quality deterioration of fish is caused by various factors, one of them is due to the activity of cathepsin enzyme. Cathepsin enzyme activity can be inhibited by enzyme inhibitors. Inhibitors of the enzyme can be obtained from fish meat tissue by separating the enzyme-inhibitor complex with heat treatment. The purpose of this research was to extract and apply the cathepsin inhibitors to inhibit deterioration of fish quality. This research was conducted in three  steps: (1) the determination of the optimum extraction temperature for extraction of cathepsin inhibitors, (2) the determination of the most potent cathepsin inhibitors with various concentrations, and (3) the application of cathepsin inhibitors in inhibiting the deterioration of fish quality. The results showed that the cathepsin inhibitors was optimally extracted at 80°C. Cathepsin inhibitors diluted using buffer with a ratio of 1: 1 had the same relative activity without dilution. The process of quality deterioration of milkfish  control in chilling temperatures occured after 504 hours (21 days) storage with a 24-hour observation time interval. The complete process during observation was pre-rigor (0 hour ), rigor mortis (96 hours), post-rigor (360 hours), and deterioration (504 hours). The process of milkfish quality deterioration treated with soaking in  cathepsin inhibitors occured after 624 hours (26 days) storage with the detailed process as follows: 0 hour (pre-rigor), 144 hours (rigor mortis), 408 hours (post-rigor), and 624 hours (deterioration). Thus fish marinated with cathepsin inhibitors achieve slower deterioration phase 5 days. Keywords: cathepsin inhibitor, deterioration, pre-rigor, rigor mortis, post-rigor, quality deterioration.